2002
DOI: 10.1097/00007632-200202010-00003
|View full text |Cite
|
Sign up to set email alerts
|

Epidural Application of Nucleus Pulposus Enhances Nociresponses of Rat Dorsal Horn Neurons

Abstract: Results suggest that somewhat pathogenic factors in the nucleus pulposus may have a crucial role in the induction of hyperalgesia. This may help to elucidate the reason why a severe pain is sometimes induced without a visually identified protrusion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
34
0
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(36 citation statements)
references
References 33 publications
1
34
0
1
Order By: Relevance
“…Transplantation of autologous NP near a spinal nerve root is frequently used in animal models of lumbar intervertebral disc herniation, 17,19,29,31,33,34,41 and NP application without compression of the nerve root and DRG produces morphologic and functional changes and blood flow impairment, 18,30,51 enhances responses of secondary neurons to noxious stimuli, 3 and causes allodynia in the hindlimb. Recently, we reported that autologous implantation of NP on a nerve root in a rat caused upregulation of fractalkine in the spinal dorsal horn, which suggests that fractalkine is associated with radicular pain.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Transplantation of autologous NP near a spinal nerve root is frequently used in animal models of lumbar intervertebral disc herniation, 17,19,29,31,33,34,41 and NP application without compression of the nerve root and DRG produces morphologic and functional changes and blood flow impairment, 18,30,51 enhances responses of secondary neurons to noxious stimuli, 3 and causes allodynia in the hindlimb. Recently, we reported that autologous implantation of NP on a nerve root in a rat caused upregulation of fractalkine in the spinal dorsal horn, which suggests that fractalkine is associated with radicular pain.…”
Section: Discussionmentioning
confidence: 99%
“…30 Previous studies have suggested that the signs of lumbar disc herniation are caused by chemical factors from the nucleus pulposus and by mechanical compression of the lumbar nerve root 3,18,27,28,30,51 and that they are mediated by proinflammmatory cytokines derived from the herniated intervertebral disc. 13,16,37 Also implicated in NP-induced nerve root injury and associated radicular pain is expression of cytokines such as IL-1, IL-6, IL-8, tumor necrosis factor-a, and cyclooxygenase-2.…”
mentioning
confidence: 99%
“…It has been known for some time that peripheral inflammatory conditions resulting in heightened pain sensitivity are characterized by an early release of TNFa at the site of inflammation. 1 Direct application of TNFa to peripheral nerve induces spontaneous electrophysiologic activity in neurons of the dorsal root ganglion (DRG), [2][3][4] and subcutaneous or epineurial application of TNFa produces nocisponsive behaviors. 5,6 A substantial body of evidence suggests that neuroimmune activation of glial cells in the dorsal horn of spinal cord results in the release of proinflammatory cytokines and plays an important role in facilitation of nociceptive neurotransmission and the development of chronic pain.…”
Section: Introductionmentioning
confidence: 99%
“…NP application without compression of the nerve root and DRG produces morphologic/functional changes and blood flow impairment 2,6,9,31) , response of secondary neurons to noxious stimuli is enhanced 1) , and allodynia in the hind limb has been demonstrated 32) . The present study showed that allodynia was induced from post -operative day 1 in the NP and MC+NP groups.…”
Section: Discussionmentioning
confidence: 99%